THE VIEWS OF MUSLIM PHILOSOPHERS ON THE THEORY OF EVOLUTION (American Journal of Research in Humanities and Social Sciences, 2024)
The article was devoted to the discussion of the views of Ibn Miskawayh and Abu Rayhan Beruni on gradual development. Philosophers' opinions on the issue reflected in the article are comparatively analyzed.